Efficacy of two mouthwashes on 3‐day supragingival plaque regrowth: a randomized crossover clinical trial. Issue 1 (2nd November 2015) - Marchetti, E; Casalena, F; Capestro, A; Tecco, S; Mattei, A; Marzo, G
Abstract: Background: The aim of this study was to evaluate the antiplaque effects of an alcohol‐free essential oil (alcohol‐free EO) mouthwash and an amine fluoride/stannous fluoride with zinc lactate (SnFl‐Zn) mouthwash compared to a positive control of chlorhexidine (CHX) mouthwash, using an in vivo plaque regrowth model of 3 days. Materials and methods: The study was designed as a double‐masked, randomized, crossover clinical trial, involving 20 volunteers to compare two different mouthwashes, using a 3‐day plaque accumulation model. After receiving thorough professional prophylaxis at baseline, over the next 3 days, each volunteer refrained from all oral hygiene measures and performed two daily rinses with 20 ml of the test mouthwashes. A 0.20% CHX rinse served as a positive control. At the end of each experimental period, plaque was assessed, and the panellists completed a questionnaire. Each subject underwent a 14‐day washout period, and then, there was another allocation. Results: The SnFl‐Zn mouthwash has shown a better inhibitory activity on plaque regrowth compared to the alcohol‐free EO mouthwash in the whole mouth (plaque index = 1.93 against 2.45, respectively), but there was less of an effect compared to the CHX group, with an overall plaque index of 1.41. The differences of 0.52 between alcohol‐free EO and SnFl‐Zn and between SnFl‐Zn and CHX and of 0.96 between alcohol‐free EO and CHX were all statistically significant ( P < 0.001). Conclusion: The alcohol‐free EO mouthwash seemed to have less of an inhibiting effect on plaque regrowth than the amine fluoride/SnFl‐Zn mouthwash and the CHX control.